Small-scale soft grippers with environmentally responsive logic gates. Issue 5 (5th April 2022) - Zhang, Xuan; Wu, Ya; Li, Yan; Jiang, He; Yang, Qinglin; Wang, Zichao; Liu, Jiahao; Wang, Yang; Fan, Xiaodong; Kong, Jie
Abstract : Small-scale soft grippers performing logical operations can be fabricated by assembling many modular blocks of stimuli-responsive hydrogels, without electronics, external control, or tethering. Abstract : Small-scale soft grippers are adaptive and deformable, and can be utilized for confined environments ( e.g., the human body). Small-scale soft grippers require logic-based computation to achieve intelligent control and perform logical analysis of the surrounding information. However, it is a great challenge to integrate electronic chips and power supplies ( i.e., batteries) on their small systems. Here, the approach provides a route to add computational capabilities via environmentally responsive logic gates in small-scale soft grippers, without electronics, external control, or tethering. Various origami-inspired grippers performing YES, NOT, XOR, AND, OR, NOR and NAND gates, respectively, were developed by stimuli-responsive hydrogels as building blocks. Although the hydrogels respond to different kinds of stimuli, their outputs are the same: a change in hydrogel size, leading to the bending of the arms of the grippers. Hence, the logic gates can be integrated easily within a gripper ( e.g., connecting an AND gate to another AND gate). Moreover, the gripper fabricated by dual-responsive hydrogels can intelligently and autonomously switch from an AND gate to an OR gate upon varied environmental stimuli. In addition, a magnetic gripper with an AND gate was fabricated that can analyse different stimuli, and capture and release the targeted object via the environmentally responsive logic gates. This strategy provides a new route to incorporate on-board perception, control and computation via environmentally responsive logic gates in small-scale soft robots and machines.